Sowing the Seeds of Seagrass Recovery Using Hessian Bags - Unsworth, Richard K. F.; Bertelli, Chiara M.; Cullen-Unsworth, Leanne C.; Esteban, Nicole; Jones, Benjamin L.; Lilley, Richard; Lowe, Christopher; Nuuttila, Hanna K.; Rees, Samuel C. (Frontiers in Ecology and Evolution, 2019)
Seagrass meadows are an important wetland habitat that has been degraded globally but has an important carbon storage role. In order to expand the restoration of these productive and biodiverse habitats methods are required, that can be used for large scale habitat creation across a range of environmental conditions. The spreading of seagrass seeds has been proven to be a successful method for restoring seagrass around the world, however in places where the tidal range is large such methods become limited by resultant water movements. Here we describe and test a method for deploying seagrass seeds of the species Zostera marina over large scales using a new, simple method ‘Bags of Seagrass Seeds Line (BoSSLine)’. This method involved planting seeds and sediment using natural fibre hessian bags deployed along strings anchored onto the seabed. When deployed in a suitable environment a 94% of bags developed mature seagrass shoots, unfortunately, one site subjected to a large storm event resulted in sediment burial of the bags and no seed germination. Bags were filled with 100 seeds with each leading to the development of 2.37 ± 2.41 mature shoots (206 ± 87 mm in length) 10 months after planting. The method was proven successful however the experiments illustrated the need to ensure habitat suitability prior to their use. The low seed success rate was comparable to other restoration studies however further trials are recommended to ensure ways to improve this rate. In conclusion, this study provides evidence for an effective, simple method ‘Bags of Seagrass Seeds Line (BoSSLine)’ for deploying seeds of the seagrass Zostera marina over large scales.